2022
DOI: 10.3390/ijerph19063253
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Associations between Adverse Childhood Experiences, Health Risk Behaviours, and Psychological Well-Being in a Convenience Sample of Lithuanian University Students

Abstract: This study examines the associations between adverse childhood experiences (ACEs), health risk behaviours, and psychological well-being among Lithuanian university students. A cross-sectional survey was carried out with a convenience sample of 393 students (80.7% females and 19.3% males) recruited from mostly undergraduate courses (96.4%) in Lithuanian universities. Participants, aged 18–25 years (21.07 ± 1.53), completed a web-based survey in which they were asked to retrospectively self-report on ACEs while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 43 publications
(69 reference statements)
0
3
0
Order By: Relevance
“…Foong et al [ 16 ] conducted a study on the relationship between Internet use and mental health in the elderly during this pandemic. Laurinaitytė et al [ 17 ] studied the association between health risk behaviors and mental health among Lithuanian university students during this pandemic. In addition, studies have shown that persistent loneliness and social isolation have adverse effects on the mental health of college students [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Foong et al [ 16 ] conducted a study on the relationship between Internet use and mental health in the elderly during this pandemic. Laurinaitytė et al [ 17 ] studied the association between health risk behaviors and mental health among Lithuanian university students during this pandemic. In addition, studies have shown that persistent loneliness and social isolation have adverse effects on the mental health of college students [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…A measure proposed to solve this problematic issue was the intervention of the university in the psychological care of students through telemedicine [ 11 ]. With regard to the mental health of students, there are also studies that were conducted before the epidemiological context [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“… Foong et al (2022) conducted a study on the relationship between Internet use and mental health in the elderly. Laurinaitytė et al (2022) studied the association between health risk behaviors and mental health among Lithuanian university students. In addition, studies have shown that persistent loneliness and social isolation have adverse effects on the mental health of college students ( Charbonnier et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%